NILAI KEARIFAN LOKAL WELIN ELA BALA DALAM TRADISI PERKAWINAN MASYARAKAT DESA BELOBATANG, KECAMATAN NUBATUKAN, KABUPATEN LEMBATA - Wutun, Hermanus Yohanes Loli; Tokan, Frans Bapa; Servatius, Rodriques (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This research is titled The Value of Local Wisdom Welin Ela Bala in the Wedding Tradition of the People of Belobatang Village, Nubatukan District, Lembata Regency. The problem formulation in this thesis is how the value of local wisdom Welin Ela Bala in the wedding tradition of the people of Belobatang Village, Nubatukan District, Lembata Regency. The theory used by the researcher to address the research problem is the theory of local wisdom and marriage. The primary data sources are informants, while secondary data sources are documents related to the research variables. Data collection techniques used include interviews, observations, and documentation. The data analysis stage is conducted through data reduction, data presentation, conclusion drawing, and then analyzed descriptively qualitatively. The research results show that (1) The Value of Consultation to describe the value of consultation in local wisdom Welin Ela Bala in the wedding tradition of the people of Belobatang Village, Nubatukan District, Lembata Regency, includes indicators of the parties involved in the consultation on the giving of the ivory dowry and the issues discussed in the dowry consultation. (2) The Value of Mutual Cooperation to describe the value of mutual cooperation in local wisdom Welin Ela Bala in the wedding tradition of the people of Belobatang Village, Nubatukan District, Lembata Regency, includes indicators of mutual cooperation in assisting the collection of ivory dowry. (3) The Value of Trust and Responsibility to describe the value of trust and responsibility in local wisdom Welin Ela Bala in the wedding tradition of the people of Belobatang Village, Nubatukan District, Lembata Regency, includes indicators of the giving of the belis dowry. Based on the above analysis, the researcher concludes that the value of local wisdom Welin Ela Bala in the wedding tradition remains preserved and maintained in the community's life through the implementation of the values of consultation, mutual cooperation, trust and responsibility, as well as good manners.